Hubungan Stres Ibu dengan Kekerasan dalam Rumah Tangga Dimasa Pandemi Covid-19 - Yusrini Yusrini; Ponirah Ponirah; Mutia Alfiah (Universitas Malahayati Lampung, 2023)
ABSTRACT The new normal background of COVID-19 has made families adapt to new habits by implementing health protocols. Mothers in the new normal period cause overwhelm in managing time and cause stress. Increased stress can be a cause of domestic violence. The purpose of the study was to determine the relationship between maternal stress and domestic violence in the new normal of Covid-19.The method and design of this study is descriptive analytic with a cross sectional approach. The research sample was 35 respondents with a total sampling method. This study used a maternal stress questionnaire and a domestic violence questionnaire. The results of the study were mild maternal stress (57%) and mild domestic violence (54%). Bivariate analysis found that there was a relationship between maternal stress and domestic violence. The result of p- value is 0.044, the value of pa (0.05). ). The conclusion of the study shows that maternal stress is mild with mild domestic violence during the New Normal Covid-19 era. Keywords: New Normal Covid-19, Domestic Violence, Maternal Stress. ABSTRAK Latar Belakang New normal covid-19 telah membuat keluarga beradaptasi dengan kebiasaan baru dengan menerapkan protokol kesehatan. Ibu dimasa new normal menyebabkan kewalahan dalam mengatur waktu dan menimbulkan stres. Meningkatnya stres dapat menjadi penyebab kekerasan dalam rumah tangga. Tujuan penelitian untuk mengetahui hubungan stres ibu dengan kekerasan dalam rumah tangga dimasa new normal Covid-19. Metode dan Desain penelitian ini adalah deskriptif analitik dengan pendekatan cross sectional. Sampel penelitian sebanyak 35 responden dengan metode total sampling. Penelitian ini menggunakan kuesioner stres ibu dan kuesioner kekerasan dalam rumah tangga. Hasil penelitian stres ibu ringan (57%) dan kekerasan dalam rumah tangga ringan (54%). Analisa Bivariat didapatkan ada hubungan antara stres ibu dengan kekerasan dalam rumah tangga. Hasil p- value 0,044, nilai pa (0,05). Kesimpulan penelitian menunjukan stres ibu ringan dengan kekerasan dalam rumah tangga ringan dimasa New Normal Covid-19. Kata Kunci: New Normal Covid-19, Kekerasan Dalam Rumah Tangga, Stres Ibu.